2022
DOI: 10.3390/su142315702
|View full text |Cite
|
Sign up to set email alerts
|

Manifold Design in a PEM Fuel Cell Stack to Improve Flow Distribution Uniformity

Abstract: In this paper, a numerical study was performed to investigate the flow distribution in a 52-cell proton exchange membrane (PEM) fuel cell stack. The non-uniformity factor and standard deviation parameters were used to determine the flow distribution uniformity. Flow channels of each bipolar plate were replaced with straight parallel channels filled with porous media to reduce computational costs. The effect of external and integrated humidifiers on the gas distribution among the channels was investigated. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The high voltage gain and reduced voltage ripple of the proposed DC-DC converter ensures a reduction of the current ripple of the system that is caused by the non-linear electrical loads. The microgrid must eliminate the lower order harmonics, otherwise it can inject a low frequency AC current to the PEMFC and subsequently cause performance disorder by shifting its polarity region [39]. Thus, due to the implementation of the high voltage gain DC-DC converter, the lower order harmonics are eliminated from the microgrid's current, which can also prevent the PEMFC from operating outside the polarization region.…”
Section: Performance Asssessment Of the Pemfcmentioning
confidence: 99%
“…The high voltage gain and reduced voltage ripple of the proposed DC-DC converter ensures a reduction of the current ripple of the system that is caused by the non-linear electrical loads. The microgrid must eliminate the lower order harmonics, otherwise it can inject a low frequency AC current to the PEMFC and subsequently cause performance disorder by shifting its polarity region [39]. Thus, due to the implementation of the high voltage gain DC-DC converter, the lower order harmonics are eliminated from the microgrid's current, which can also prevent the PEMFC from operating outside the polarization region.…”
Section: Performance Asssessment Of the Pemfcmentioning
confidence: 99%
“…Lebeak et al [7], observed jet flow behaviour when the circular geometry changes to rectangular when entering to manifold which causes the flow maldistribution. The more flow distribution in the final 20% of the channels than initial channels due to high velocity [8], reducing channel hydraulic diameter and increasing the manifold dimension [9], reducing channel width and increasing pressure drop [10], providing double inlet and outlet manifold configurations [11] are some of the findings for flow distribution in manifold as well as in flow channel. This work emphasis the effect of manifold and distributor dimension on anode side of a 5-cell stack with serpentine flow field.…”
Section: Introductionmentioning
confidence: 99%